Great Canadian Lagerstätten 5. Crawford Lake – A Canadian Holocene Lacustrine Konservat-Lagerstätte with Two-Century-Old Viable Dinoflagellate Cysts - Krueger, Andrea; McCarthy, Francine (Geoscience Canada)

(untitled) (The Geological Association of Canada, 2016)
SUMMARYIn addition to commonly preserved microfossils like pollen and diatoms, the varved sediments of Crawford Lake, Ontario, contain the fossilized remains of otherwise rare microfossils. Bottom water anoxia resulted from the physiography of this small, deep lake and enhanced biochemical oxygen demand (BOD) during two distinct phases of human settlement: prehistoric Iroquoians (approximately 1268–1486 CE) and historic Euro-Canadians (since 1822 CE). The exceptional preservation of delicate organic-walled microfossils like rotifer loricae and cellulosic dinoflagellate thecae provides unparalleled insights into a Holocene freshwater lake ecosystem and allows the biological and taphonomic components of the fossil assemblage to be isolated. Bottom water anoxia may also have increased the longevity of cell contents: resting cysts of Parvodinium [Peridinium] inconspicuum (Lemmermann) Carty and Peridinium volzii Lemmermann. These were germinated from varves deposited nearly two centuries ago, extending the known span of viability of dinoflagellates.